Revisiting “Pedagogy of Discomfort” Through the Combined Lenses of “Inconvenience” and “Affective Infrastructure”: Pedagogical and Political Insights - Zembylas, Michalinos (Philosophical Inquiry in Education, 2023)
This paper seeks to revisit the concept of “pedagogy of discomfort” through the combined lenses of Lauren Berlant’s work on “inconvenience” and recent theorization of “affective infrastructure” to clarify how an infrastructural understanding of “discomfort-as-inconvenience” might provide deeper insights about the pedagogical and political risks and possibilities of discomfort. In particular, the paper highlights three insights: first, it expands our understanding of discomfort by situating it in the broader context of the inconvenience of other people, as an ethics and politics of coexistence; second, it calls for a contextual approach of a pedagogy of discomfort that examines discomfort as a multifaceted affective event entangled with other material, social, and political elements; and third, it enables educators to create environments that could enrich the moral and political potential of a pedagogy of discomfort, by paying attention to the affective conditions in which students and educators find themselves when they encounter different manifestations of discomfort-as-inconvenience.